1981
DOI: 10.3758/bf03206144
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual presentation demonstrates that selective adaptation in speech perception is purely auditory

Abstract: . Both auditory and phonetic processes have been implicated by previous results from selective adaptation experiments using speech stimuli. It has proved difficult to dissociate their individual contributions because the auditory and phonetic structure of conventional acoustical stimuli are mutually predictive. In the present experiment, the necessary dissociation was achieved by using an audiovisualadaptor consisting of an acoustical [bE] synchronized to a video recording of a talker uttering the syllable [g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
4
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 22 publications
(31 reference statements)
12
88
4
2
Order By: Relevance
“…Others however (e.g., Sawusch, 1977), showed that the size of selective speech adaptation depends upon the degree of spectral overlap between the adapter and test sound, and that most, if not all of the effect is auditory rather than phonetic. A similar conclusion was reached by Roberts and Summerfield (1981). They exposed listeners to audiovisual congruent (auditory /b/ with lipread /b/) or incongruent adapter stimuli (auditory /b/ with lipread /g/) and obtained similar aftereffects, despite the fact that the adapters were perceived differently.…”
Section: -Introductionsupporting
confidence: 48%
See 3 more Smart Citations
“…Others however (e.g., Sawusch, 1977), showed that the size of selective speech adaptation depends upon the degree of spectral overlap between the adapter and test sound, and that most, if not all of the effect is auditory rather than phonetic. A similar conclusion was reached by Roberts and Summerfield (1981). They exposed listeners to audiovisual congruent (auditory /b/ with lipread /b/) or incongruent adapter stimuli (auditory /b/ with lipread /g/) and obtained similar aftereffects, despite the fact that the adapters were perceived differently.…”
Section: -Introductionsupporting
confidence: 48%
“…For example, Roberts and Summerfield (1981) demonstrated that adaptation was induced by the auditory component, whereas the phonetic label attached to the adapting stimulus had no effect. Here we also observed that equal amounts of selective adaptation were obtained for listeners in speech or non-speech mode.…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samuel's results contrast with those of Roberts and Summerfield (1981) and Saldaña and Rosenblum (1994), who used the McGurk effect (McGurk & McDonald 1976) to investigate whether adaptation was driven by the acoustic form of the input or by its phonemic percept. The Saldaña and Rosenblum study took advantage of the fact that an auditory /ba/ presented with a video of a spoken /va/ is perceived as /va/.…”
Section: Phonemic Restoration and Selective Adaptationcontrasting
confidence: 42%